V2O3/C composite fabricated by carboxylic acid-assisted sol-gel synthesis as anode material for lithium-ion batteries - Zakharova, Galina S.; Thauer, Elisa; Enyashin, A. N.; Deeg, Lukas; Zhu, Q.; Klingeler, Rüdiger (Journal of sol gel science and technology, 2021)
The potential battery electrode material V2O3/C has been prepared using a sol-gel thermolysis technique, employing vanadyl hydroxide as precursor and different organic acids as both chelating agents and carbon sources. Composition and morphology of resultant materials were characterized by X-ray diffraction, Raman spectroscopy, scanning and transmission electron microscopies, physical sorption, and elemental analysis. Stability and electronic properties of model composites with chemically and physically integrated carbon were studied by means of quantum-chemical calculations. All fabricated composites are hierarchically structured and consist of carbon-covered microparticles assembled of polyhedral V2O3 nanograins with intrusions of amorphous carbon at the grain boundaries. Such V2O3/C phase separation is thermodynamically favored while formation of vanadium (oxy)carbides or heavily doped V2O3 is highly unlikely. When used as anode for lithium-ion batteries, the nanocomposite V2O3/C fabricated with citric acid exhibits superior electrochemical performance with an excellent cycle stability and a specific charge capacity of 335 mAh g−1 in cycle 95 at 100 mA g−1. We also find that the used carbon source has only minor effects on the materials’ electrochemical performance.